Cyclopeptide alkaloid and lignans from Antidesma hainanensis Merr. - Viet Cuong, Le Canh; Trang, Do Thi; Nhiem, Nguyen Xuan; Yen, Pham Hai; Tai, Bui Huu; Tuan Anh, Hoang Le; Huong, Le Mai; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2016)
Cyclopeptide alkaloid lotusanine B (1) and three lignans (-)-lyoniresinol (2), (+)-lyoniresinol 3α-O-β-D-glucopyranoside (3), and (+)-isolariciresinol 3α-O-β-D-glucopyranoside (4) were isolated from the methanol extract of the Antidesma hainanensis leaves. Their chemical structures were successfully determined using NMR and ESI-MS analysis as well as in comparison with the reported data. Especially, the NMR data of lotusanine B were first confirmed by 2D-NMR spectroscopies and reassigned. This is the first report of lotusanine B from Euphorbiaceae family.